Effectiveness of seed oil formulations of Azadirachta indica (A.) Juss and Barringtonia asiatica (L.) Kurz in controlling aphids (Aphis gossypii glover) on Strawberry (Fragaria x ananassa duch) plants - Sudarjat, Sudarjat; Djaya, Luciana; Muhammad, Ardhi (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2023)
Strawberry production is often decreased by plant pest infestation in the field. One of the major pests is Aphis gossypii. Strawberry farmers typically use synthetic chemical pesticides to control aphid, however, this can pose serious environmental and human health problems if done continuously. The use of synthetic chemical pesticides can be minimized by using botanical pesticides, as they are safer for human health and the environment. Botanical pesticides that can be used include neem seed extract (Azadirachta indica) and sea poison tree (Barringtonia asiatica). The objective of this research was to test the effectiveness of neem and sea poison tree seed oil formulations against A. gossypii on strawberry plants. The experiment was conducted at CV Bumi Agro Technology, Lembang, from April 2023 to August 2023, arranged in the randomized complete block design consisting of 7 treatments with 4 replications. The treatments were application of neem and sea poison tree seed oil at different concentrations, as follow: (A) Control, (B) Abamectin 0.15%, (C) Neem Oil 2%, (D) Neem seed oil 50 EC 2%, (E) Neem seed oil 50 EC 1%, (F) Sea poison tree seed oil 30 SC 2%, and (G) Sea poison tree seed oil 30 SC 1%. The results showed that neem and sea poison tree seed oil formulations at the concentration of 2% were effective in controlling A. gossypii on strawberry plants.